A novel bisoxazoline/Pd composite microsphere: a highly active catalyst for Heck reactions1. Issue 93 (11th October 2015) - Wang, Junke; Zong, Yingxiao; Yue, Guoren; Hu, Yulai; Wang, Xicun
<x xml:space="preserve">Abstract</x> A novel bisoxazoline/Pd microsphere catalyst was successfully prepared.